Resolusi Konflik Konsumen di Kota Padang - Ovy Riana Irawan; Zuldesni Zuldesni; Elfitra Elfitra (Department of Sociology, Faculty of Social and Political Sciences, Universitas Andalas, 2021)
Consumer conflict is the reality of capitalistic society. To resolve this, the Indonesian government established the Consumer Dispute Settlement Agency (BPSK). The article answers the question of how BPSK involve in resolving a consumer conflict in Padang Cuty. Using qualitative approach, the results show that in resolving conflicts, the involvement of BPSK is based on the degree of desire of the parties. BPSK uses three mechanism: Reconcilisation, mediation, and arbitrase. Among the three methods, there are different degrees of intervention of BPSK in accordance with the agreement and wishes of both parties to the dispute. For conciliation and mediation, this stage is more characteristic of BPSK, namely conducting discussions first to relieve and take a good path for both parties without a complicated and binding trial. If both parties fail to make peace, then arbitration is the last resort to resolve the issue.